Epicutaneous immunotherapy for food allergy: a systematic review and meta-analysis - Xiaohong Xiang; Jingwei Hu; Rangui Sachu; Chonghua Gao; Hongyan Niu; Yi Gao; Shiju Chen; Xiaotian Cui; Xiang Li (Systematic Reviews)
Abstract Background There is ongoing debate about the safety and efficacy of epicutaneous immunotherapy (EPIT) in treating food allergies. The systematic review and meta-analysis aimed to evaluate the safety and efficacy of EPIT. Methods We systematically searched international trial registers (ClinicalTrials.gov), PubMed, Embase, the Cochrane Central of Controlled Trials (CENTRAL), and Web of Science from the inception of the database until June 25, 2023. Two authors independently screened potential studies based on the following criteria: food allergy, epidermal immunotherapy, and randomized controlled trials(RCTs). The risk-of-bias assessment was performed using the Cochrane risk-of-bias 2 (ROB 2) tool. The primary outcomes included desensitization, local adverse events, systemic adverse events, and quality of life. Secondary outcomes included epinephrine utilization, topical medication utilization, and severe adverse events. We assessed certainty of evidence by the GRADE approach. Results Ten studies involving 1970 participants were included. Ten high-quality RCTs focusing on peanut allergy and cow’s milk allergy were included in the analysis. The meta-analysis revealed that EPIT promoted desensitization in patients with food allergy (RR 2.11, 95% CI 1.72–2.58; I 2 = 0%, high certainty), particularly in aged ≤ 11 years (RR 3.84, 95% CI 2.39–6.26; I 2 = 34%). Additionally, treatment duration ≥ 52 weeks was found to increase immune tolerance (RR 3.37, 95% CI 2.39–4.75; I 2 = 13%). Patients who undergo EPIT treatment not only raised the local adverse reactions (RR 1.63, 95% CI 1.10–2.41; I 2 = 82%, low certainty) but also raised systemic adverse reactions (RR 1.52, 95% CI 1.01–2.28; I 2 = 0%, high certainty). Conclusion After EPIT treatment, patients with food allergy can effectively increase their immune tolerance to food. However, it also significantly increases mild-to-moderate anaphylaxis. There is limited data on the impact of EPIT on quality of life and other food allergic diseases, indicating a need for further research.